Implikasi Pembelajaran Model STEAM melalui LKPD ecoprint terhadap kreativitas dan kompetensi kewirausahaan siswa - Aulia, Vira Safitri; Setiono, Setiono; Ratnasari , Jujun; Fitriani, Herni (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
Background: Innovation in learning methods is essential to improve students' creativity and entrepreneurial competence. The STEAM learning model with ecoprint-based Student Worksheets (LKPD) is one method that can be used. This study aims to determine the effect of the STEAM learning model through eco print-based Student Worksheets (LKPD) on students' creativity and entrepreneurial competence with students whose learning uses conventional learning models (discovery learning). Method: This study used a quasi-experimental method with a Non-equivalent control group design. The research sample selection technique used purposive sampling of class X students at a high school in Sukabumi City for the 2023/2024 academic year. Results: The study showed that students' creativity in the experimental class obtained an average value of 82±0.24 percent and entrepreneurial competence of 86±0.38 percent, both in the outstanding category. The hypothesis test results obtained a significance value of Sig (2-tailed) 0.000 for both variables, so H0 was rejected and H1 was accepted. Conclusion: This study implies that using the STEAM model through Ecoprint-based LKPD can be an alternative effective learning model in improving students' creativity and entrepreneurial competence. The implications of this study indicate the need for broader development of the Ecoprint project-based STEAM model to support practical and innovative learning.